Application of Ethics and Science in Life - Ramadhani, Bima; Putri, Naja Jessyka Maulani; Winarno, Agung (Intelektualitas Jurnal Penelitian Lintas Keilmuan, 2024)
Essentially, ethics and morals are guidelines for human action, and science seeks to explain reality as it is. Science is a systematic effort to investigate, discover and improve human understanding of various aspects of human nature. These aspects are limited to produce clear formulations. By limiting the range of their views, science provides confidence, and this confidence comes from its limitations. Science is not just knowledge, but encapsulates a body of knowledge that is based on recognized theories and can be tested with a set of recognized methods in a particular field.